2000
DOI: 10.1038/sj.leu.2401668
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis of prognostic factors in patients with refractory and relapsed acute myeloid leukemia undergoing sequential high-dose cytosine arabinoside and mitoxantrone (S-HAM) salvage therapy: relevance of cytogenetic abnormalities

Abstract: To improve the basis for the stratification of patients with refractory and relapsed acute myeloid leukemia (AML) univariate and multivariate analyses of prognostic factors were performed in 254 patients (median age 50 years, range 18-74) undergoing S-HAM salvage chemotherapy during two consecutive prospective trials of the German AML Cooperative Group. In a multivariate analysis, duration of the first complete remission (CR) was the only factor associated with time to treatment failure (P = 0.0223). Disease-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
39
0
5

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 32 publications
9
39
0
5
Order By: Relevance
“…[17][18][19][20][21] A recurrent observation, also found in the present study, was that the duration of first CR strongly influenced second CR achievement and survival from reinduction. [17][18][19][20][21] In a large even if quite old study from Houston, duration of the initial remission positively correlated with a favorable karyotype including inv(16), t(8;21) and t(15;17) as well as with a lower incidence of antecedent hematologic disorders, high WBC and elevated creatinine or lactic acid dehydrogenase level. 17 In a more recent study from Vienna, favorable or normal cytogenetics was also associated with a better outcome after second CR.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…[17][18][19][20][21] A recurrent observation, also found in the present study, was that the duration of first CR strongly influenced second CR achievement and survival from reinduction. [17][18][19][20][21] In a large even if quite old study from Houston, duration of the initial remission positively correlated with a favorable karyotype including inv(16), t(8;21) and t(15;17) as well as with a lower incidence of antecedent hematologic disorders, high WBC and elevated creatinine or lactic acid dehydrogenase level. 17 In a more recent study from Vienna, favorable or normal cytogenetics was also associated with a better outcome after second CR.…”
Section: Discussionsupporting
confidence: 85%
“…The importance of diagnostic cytogenetics as prognostic factor for outcome in patients with AML led investigators to compare SCT and chemotherapy within each cytogenetic subgroup. Results show that SCT in first CR does not appear to benefit to relatively good-risk AML patients, as those with t (8,21), inv (16/t(16;16) or a normal karyotype (NN group). 8,9 The French AML Intergroup has recently reported the results of two large retrospective studies conducted in patients with t(8;21) and inv(16) AML, which both confirm this observation in patients with core binding factor (CBF) AML.…”
Section: Transplantation; Prognosismentioning
confidence: 97%
“…We have previously reported that the proportion of patients with a favourable karyotype is high among patients with a duration of second CR of more than 2 years. 26 Kern et al 27 found that unfavourable cytogenetics were associated with a lower rate of second CR and was a poor prognostic factor with regard to survival after first relapse. In the above-mentioned studies, a validated prognostic classification of cytogenetics (like the classification according to the United Kingdom Medical Research Council (MRC)) was not yet available and clear data on OS and DFS according to the cytogenetic risk categories were not provided.…”
Section: Introductionmentioning
confidence: 99%
“…Because follow-up data from the AML-CG 20 study were included into the database we were able to confirm the prognostic relevance of specific cytogenetic or molecular genetic anomalies. 11,[21][22][23][24][25] The detection of new chromosomal aberration patterns is supported by a specific program providing frequency distributions of chromosome breakage points ordered by disease.…”
Section: Data Monitoring and Analysis Of A Complex Databasementioning
confidence: 99%
“…The integration of clinical and genetic data generates new scientific results; some examples in the field of leukemia research are provided in Refs 11,[21][22][23][24][25] Integration of clinical and scientific documentation requires significant efforts, but is feasible and provides better data quality and therefore faster research results. Before the integrated database was available, we lost up to 50% of cases when we combined several data sources automatically due to mismatch of patient demographic data and other inconsistencies.…”
Section: Impact Of Integrating Clinical and Genetic Datamentioning
confidence: 99%